Analisis Kemampuan Spasial Peserta Didik Ditinjau Dari Gender dan Self Efficacy Pada Materi Bangun Ruang Sisi Datar - Dino, Paternus Surya; Hamdani; Yundari (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to provide an in-depth analysis of the spatial ability of ninth-grade students at SMP Kasih Yobel Singkawang in the subject of flat-sided solid geometry, examined through the psychological variable of self-efficacy and the demographic variable of gender. Using a descriptive qualitative approach, data were collected through a spatial ability test, a self-efficacy questionnaire, and in-depth interviews with subjects selected via purposive sampling. The results indicate a strong positive correlation between self-efficacy and spatial ability. Students with high self-efficacy demonstrated significantly superior performance, characterized by perseverance and effective problem-solving strategies, compared to students with low self-efficacy who tended to be hesitant, give up easily, and struggled with mental visualization. Significantly, this study also found that female students exhibited superior spatial ability across all measured components—spatial perception, relations, and visualization—compared to male students. These findings affirm that affective factors, such as self-belief, are crucial predictors of cognitive success in geometry and challenge gender stereotypes related to spatial abilities.